The Impact of Parents and Peers on the Saving Behavior of Nepalese Youth - Goit, Jogindar (Nepalese Journal of Management Science and Research, 2023)
The goal of this study is to look at the relationship between peers’ influence and parents’ influence on the saving behavior of Nepalese youth and the impact of peers’ influence and parents’ influence on the saving behavior of Nepalese youth. The research has used primary sources of data. A well-structured questionnaire was designed to collect data from 250 respondents. The convenience sampling technique was used to select a sample for the study. Moreover, Cronbach’s Alpha was assessed to test reliability. The correlational and casual research designs were used. The findings revealed that there was a positive and significant relationship between peers’ influence and parents’ influence on the saving behavior of Nepalese youth and peers’ influence and parents’ influence have a significant impact on the saving behavior of Nepalese youth. This study is useful for those saving behavior seekers as parents’ influence is a major factor in many facets of life in Nepalese communities. Children are taught to respect their parents and they have the power and obligation. Since parents have such a big impact on young people, they should seize the chance to let their kids watch them practice good saving habits as a way of preparing them for life in the adult world.